PENGARUH MEDIA KARTU BILANGAN TERHADAP HASIL BELAJAR MATEMATIKA MATERI PENGURANGAN DI KELAS II SD BERTINGKAT NAIKOTEN - Patri E.Tefamnasi; Alvin Javier Hano; Chintia M.P. Ati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low mathematics learning outcomes of second-grade students at SD Bertingkat Naikoten, particularly on subtraction material. The problem was caused by the use of conventional teaching methods and the lack of attractive and interactive learning media. One alternative that can be used to overcome this problem is number card media. This study aimed to determine the effect of using number card media on students' mathematics learning outcomes in subtraction material at SD Bertingkat Naikoten. This study employed a quantitative approach using an experimental method with a Pretest-Posttest Control Group Design. The population consisted of all second-grade students of SD Bertingkat Naikoten, totaling 31 students. The sample comprised 15 students in the experimental class and 16 students in the control class. Data were collected through tests, observations, and documentation. The research instrument consisted of multiple-choice questions administered during the pretest and posttest. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing (t-test) with the assistance of SPSS softwareThe results showed that the use of number card media had a positive effect on students' mathematics learning outcomes. This was indicated by the higher posttest mean score of the experimental class compared to the control class. Furthermore, the hypothesis testing results revealed that the significance value was less than 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, it can be concluded that the use of number card media has a significant effect on mathematics learning outcomes in subtraction material for second-grade students at SD Bertingkat Naikoten.